2018
DOI: 10.1002/jor.23910
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between in vitro and in vivo cartilage overloading studies based on a systematic literature review

Abstract: Methodological differences between in vitro and in vivo studies on cartilage overloading complicate the comparison of outcomes. The rationale of the current review was to (i) identify consistencies and inconsistencies between in vitro and in vivo studies on mechanically‐induced structural damage in articular cartilage, such that variables worth interesting to further explore using either one of these approaches can be identified; and (ii) suggest how the methodologies of both approaches may be adjusted to faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 136 publications
(249 reference statements)
0
12
0
Order By: Relevance
“…Other reviews [ 139 , 140 ] have well described how articular cartilage explant models have used various types of injurious compression protocols to simulate mechanical injury and have demonstrated that, despite differences in protocols, these models show that they similarly and successfully induce the clinically observed pathologies following trauma to the knee joint. Hence, the mechanically-induced injury of articular cartilage leads to a significant increase in chondrocyte death, ECM loss, expression of matrix-degrading enzymes and a decrease in the COL2 gene and, to some extent, an increase in inflammatory cytokines even in the absence of inflammatory cells, such as macrophages [ 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 ].…”
Section: Results Of the In Vivo Ex Vivo And In Vitro Models That mentioning
confidence: 99%
“…Other reviews [ 139 , 140 ] have well described how articular cartilage explant models have used various types of injurious compression protocols to simulate mechanical injury and have demonstrated that, despite differences in protocols, these models show that they similarly and successfully induce the clinically observed pathologies following trauma to the knee joint. Hence, the mechanically-induced injury of articular cartilage leads to a significant increase in chondrocyte death, ECM loss, expression of matrix-degrading enzymes and a decrease in the COL2 gene and, to some extent, an increase in inflammatory cytokines even in the absence of inflammatory cells, such as macrophages [ 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 ].…”
Section: Results Of the In Vivo Ex Vivo And In Vitro Models That mentioning
confidence: 99%
“…This justifies vigorous efforts to systematically study the molecular basis of disease onset and progression with the aim to develop innovative therapeutic strategies that interfere with the complex OA pathogenesis [ 2 , 3 ], currently culminating in multi-omics approaches to identify relevant molecular signatures [ 4 ]. Obviously, the strategic combination of work on clinical material with tailored in vitro models would be helpful to generate meaningful pathobiological results and improve translatability of new knowledge into clinical practice [ 5 ]. From a practical perspective, two-dimensional (2D) cell cultures have been considered as the starting point on the way to mimic an in situ-like microenvironment in vitro .…”
Section: Introductionmentioning
confidence: 99%
“…There are several limitations to the present study. First, in addition to the magnitude of load, injuries would also be affected by loading rate 31–33 , which cannot be separated in the present drop‐tower impacting configuration. Therefore, the rabbit model cannot completely simulate motor vehicle dashboard‐type injury.…”
Section: Discussionmentioning
confidence: 99%